PERNIKAHAN BEDA AGAMA: KAJIAN NORMATIF DAN PSIKOLOGIS DALAM KONTEKS MASYARAKAT URBAN - Dul Jalil (LPPM STAI Muhammadiyah Probolinggo, 2025)
Marriage is a fundamental aspect of human life, governed by religion, custom, and state law. In Indonesia, where five religions are officially recognized, interfaith social interactions are common, including in marriage. Although most religions in Indonesia prohibit interfaith marriages, such unions still occur, particularly in urban communities. This study aims to examine the dynamics of interfaith marriage and the reasons behind couples choosing to marry despite religious and legal prohibitions. Using a case study method with normative and psychological approaches, data were collected through interviews with interfaith couples. The findings show that these couples often proceed with marriage based on emotional and spiritual compatibility. They consider interfaith marriage a khilafiyah issue—open to interpretation (ijtihad)—and believe such unions are morally and spiritually valid. This perspective contrasts with the dominant views of religious scholars and Indonesia’s legal framework, which generally do not recognize interfaith marriages.